Influence of Biochar Fortified with Fungi (Termitomyces) on Carbon Stock, Flux, and Yield of Groundnut - Wakili, Habib Dahiru; Abdulsalam, Khalid; Wakili, Habib Hafsah (CV. Literasi Indonesia, 2024)
The study was conducted to investigate carbon stock, flux, and sequestration potential as well as the response of groundnut (yield) to different fortification approaches. A greenhouse experiment was conducted using four treatment combinations, fortified biochar with T. albuminosus (B + T), biochar (B), T. albuminosus, and control laid in a Complete Randomized Design (CRD). The result showed increased carbon sequestration, stock, and a subsequent decrease in carbon emission in treatment B + T relative to other treatments. Untreated samples recorded the lowest values with 3.69 g kg-1 sequestered carbon 24.97 kg ha- stock 4.92% carbon emission and a net flux of -20.70. The highest groundnut yield was also recorded in the B + T treatment with a value of 1131.10 kg ha-1. However, biochar treatment recorded the highest biomass and stover yield 5.62 t ha-1 and 3.82 t ha-1 respectively. In conclusion, the Fortification of biochar with T. albuminosus proved efficient in improving carbon sequestration, increasing carbon stock, and reducing emission as well as other nutrients in soils under cultivation. Also, using B + T as an amendment under optimal growth conditions is recommended for better groundnut production. The study's constraints lie in its execution within controlled greenhouse settings, potentially limiting its applicability to real-world field conditions. Thus, caution should be exercised when extending these findings to field applications, ensuring the validation of the approach's effectiveness.